IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS AT MUTIARA DELIMA CLINIC, SAWOO, PONOROGO - Putri Nur Alfiana; Dwi Nurjayanti (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Electronic Medical Records (EMR) represent a form of digital transformation in the healthcare sector that aims to improve efficiency, security, accuracy, and service quality, particularly in patient registration, healthcare service delivery, data management, and medical record storage processes. This study aims to comprehensively examine the implementation of EMR at Klinik Mutiara Delima Sawoo Ponorogo, focusing on the aspects of registration, service provision, data management, and storage systems. The research method used is descriptive qualitative with a case study approach. Data were collected through observation and in-depth interviews with relevant informants involved in the EMR implementation process. The results of the study indicate that EMR has been implemented in most healthcare service processes, providing support for more effective and organized medical record management. However, several components of implementation remain suboptimal, including the unavailability of electronic signature authentication facilities and the continued use of manual procedures for BPJS (national health insurance) claim processing. These limitations affect the optimization of EMR utilization in supporting integrated healthcare services. Therefore, improvements in technological infrastructure, system development, and continuous training for healthcare staff are needed to ensure the successful and comprehensive implementation of EMR. Strengthening these aspects is expected to enhance the effectiveness, security, and sustainability of digital healthcare services.